2012
DOI: 10.1097/iae.0b013e31825be87f
|View full text |Cite
|
Sign up to set email alerts
|

Topical Bromfenac as an Adjunctive Treatment With Intravitreal Ranibizumab for Exudative Age-Related Macular Degeneration

Abstract: Topical bromfenac might reduce the frequency of ranibizumab over 6 months in eyes with relatively small age-related macular degeneration lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 32 publications
4
34
4
1
Order By: Relevance
“…CMT reduction was significantly higher (−37.1 µm) in patients receiving combination treatment (table 2 and figure 2), although there were no differences in either visual acuity or number of injections between the two groups. This finding is in contrast with the findings of a recent study by Gomi et al ,16 in which the authors reported a reduction in the frequency of ranibizumab injections over 6 months when topical bromfenac was used as an adjunctive treatment with ranibizumab. However, in addition to the differences in the pharmacological properties of bromfenac and ketorolac, another point of difference was that Gomi et al 16 administered just one ranibizumab injection and then treated the patients on an as-needed basis; these differences may have caused the significant difference in the number of injections required.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…CMT reduction was significantly higher (−37.1 µm) in patients receiving combination treatment (table 2 and figure 2), although there were no differences in either visual acuity or number of injections between the two groups. This finding is in contrast with the findings of a recent study by Gomi et al ,16 in which the authors reported a reduction in the frequency of ranibizumab injections over 6 months when topical bromfenac was used as an adjunctive treatment with ranibizumab. However, in addition to the differences in the pharmacological properties of bromfenac and ketorolac, another point of difference was that Gomi et al 16 administered just one ranibizumab injection and then treated the patients on an as-needed basis; these differences may have caused the significant difference in the number of injections required.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in contrast with the findings of a recent study by Gomi et al ,16 in which the authors reported a reduction in the frequency of ranibizumab injections over 6 months when topical bromfenac was used as an adjunctive treatment with ranibizumab. However, in addition to the differences in the pharmacological properties of bromfenac and ketorolac, another point of difference was that Gomi et al 16 administered just one ranibizumab injection and then treated the patients on an as-needed basis; these differences may have caused the significant difference in the number of injections required. Moreover, they recruited eyes with thinner CMT than those noted in our study (365±62 vs 417±87.7 in the combination groups).…”
Section: Discussioncontrasting
confidence: 99%
“…A past study indicated that bromfenac decreased VEGF expression through the antioxidant protein heme-oxygenase 1-dependent pathway in an experimental rat model and inhibited choroidal neovascularisation 25. Clinical studies in age-related macular degeneration also revealed the usefulness of synergistic effects of topical bromfenac on anti-VEGF treatments for reduction of FT,13 and in the decrease of a number of anti-VEGF drug injections 14. Also, in the ME secondary to BRVO, VEGF expression and retinal inflammation are thought to play a key role in pathogenesis; thus, the combined therapy of anti-VEGF and anti-inflammatory drugs should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous similar prospective studies,13 14 sample size was 30–40; thus, at least 40 eyes were required. The minimum required per-group sample size from the results of this study (probability level=0.05, desired statistical power level=0.8, change to be detected between the two groups=1.0 time of injection, expected SD=1.2) was 14 each, which is <21 eligible eyes in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation